Competent realisation of cooperative spectrum sensing in cognitive radio systems. (10th April 2015) - Pavithra, S.; Karthikeyan, S.; Sonti, V.J.K. Kishor; Jayashri, S.
Cognitive radio is widely expected to be the next Big Bang in field of wireless communications. The objective of cognitive radio is to enhance the spectrum utilisation efficiency. Spectrum sensing, a challenging task of cognitive radio helps in opportunistic spectrum access. Cooperative spectrum sensing mitigates these effects of fading, shadowing and uncertainties in normal sensing at the cost of energy consumption. Energy consumption in cooperative spectrum sensing is due to computation of full spectrum FFT. This paper aims at the design of cooperative spectrum sensing unit in a cognitive radio system. It present a coprocessor for computing reduced point FFT, a block for the detection of spectrum hole, a fusion centre for combining the decision from different users and a special prediction block for improving performance of cooperative spectrum sensing. This idea reduces the computation to one fourth. The simulations are done using Xilinx ISE design suit 12.1 and ModelSim and synthesised using VerilogHDL.